2018 Atmospheric and Space Environments Conference 2018
DOI: 10.2514/6.2018-3970
|View full text |Cite
|
Sign up to set email alerts
|

Total Temperature Measurements Using a Rearward Facing Probe in Supercool Liquid Droplet and Ice Crystal Clouds

Abstract: This paper presents an analysis of local total temperature and humidity experimental measurement taken in atmospheric ice cloud flows. The measurements were obtained in a series of tests in NASA's Propulsion Systems Laboratory. The probe used in the tests is referred to as the Rearward Facing Probe which was designed to mitigate the contamination effects of ice accretion and ingestion into the probe. The data provided important insights in the interaction of the ice cloud and the atmospheric flow. For the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A comparison between the commercial off the shelf total air temperature sensor and the in-house rearward facing probe cloud-on air temperature and specific humidity are reported in Ref. [22]. For particle sizing, only the curve fits to the initially-processed data are described.…”
Section: Cloud Characterization and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison between the commercial off the shelf total air temperature sensor and the in-house rearward facing probe cloud-on air temperature and specific humidity are reported in Ref. [22]. For particle sizing, only the curve fits to the initially-processed data are described.…”
Section: Cloud Characterization and Resultsmentioning
confidence: 99%
“…[23], while a description of the air temperature and humidity, both cloud off and cloud on, can be found in Ref. [22]. This characterization effort began with new cloud uniformity objectives -to push the cloud as much as possible to the edges of the duct.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and humidity measurements were made at the duct exit plane using a Rearward Facing Probe (RFP) [18]. In addition, a humidity measurement was made in the plenum -the inlet for this measurement was located on the upper wall of the plenum upstream of the spray bars.…”
Section: Aerothermal and Humidity Measurementsmentioning
confidence: 99%
“…Total temperature measurements are particularly challenging in this test environment as described in Ref. [3]. This is because of the potential to ingest ice crystals or liquid water at the probe's inlet and for ice to accrete on the probe's body, which can result in a contaminated probe measurement.…”
Section: Total Temperature Measurement and Calibrationmentioning
confidence: 99%
“…Bartkus et al [1,2] reported on both experimental data obtained in the NASA PSL and numerical results obtained using a thermodynamic model (Thermodynamically Coupled Air-Droplet Icing Wind Tunnel Model, TADICE) that demonstrated changes in air temperature and humidity as a result of the thermal exchange with the icing cloud. A more recent study [3], compared total temperature and humidity measurements of the cloud flow using a rearward facing probe (RFP) with the TADICE model which showed reasonably good agreement. The experimental data however was limited to a few tests within a limited range of parameters.…”
Section: Introductionmentioning
confidence: 99%